Rancangan Kampung Tematik Masjid Sekayu 1413 Menjadi Destinasi Wisata - Wildan Rizqyaji Madjid; Gabriel Malvin Goklas; Rina Kurniati (Jurnal Riptek, 2022)
The Thematic village of Sekayu Mosque 1413 has historical tourism potential which can be seen from historical heritage buildings in the form of the Sekayu 1413 Mosque building, and other historical buildings. The Thematic Village of Sekayu Mosque 1413 is not only focused on mosque buildings and ancient houses that have historical value, there are also other activities that can be an attraction for tourism that comes. The Thematic Village of Sekayu Mosque 1413 has several problems from infrastructure, economic, and social aspects. The purpose of this research project is to formulate a design concept and recommendations for the development of the Thematic Village of the Sekayu Mosque 1413 into a tourist destination. The data collection method of this research was carried out through literature review, interviews, and field observations. This research produces a concept that is in accordance with the characteristics of the area, namely the concept of Sustainable Historical Tourism. From this concept, several planning recommendations can be formulated that focus on infrastructure, economic, and social aspects according to the results of the Gap analysis which are compared with the tourism theory of the Sustainable Historical Tourism concept. These recommendations are expected to support the development of the Sekayu Mosque 1413 Thematic Village tourism with the concept of Sustainable Historical Tourism.